The cold dish - Johnson, Craig, 1961- (Johnson, Craig, 1961- Walt Longmire mystery, 2005)
After decades of peace between the white and Native American communities of early American Wyoming, a young man who was once convicted for raping a Cheyenne girl is found dead, prompting sheriff Walt Longmire, his deputy Victoria Moretti, and friend Henry Standing Bear to investigate.